PLU-1 is an H3K4 demethylase involved in transcriptional repression and breast cancer cell proliferation. - Yamane, K; Tateishi, K; Klose, R; Fang, J; Fabrizio, L; Erdjument-Bromage, H; Taylor-Papadimitriou, J; Tempst, P; Zhang, Y (2007)
Posttranslational modification of chromatin by histone methylation has wide-ranging effects on nuclear function, including transcriptional regulation, maintenance of genome integrity, and epigenetic inheritance. The enzymes utilized to place histone methylation marks are well characterized, but the identity of a histone demethylation system remained elusive until recently. The discovery of histone demethylase enzymes capable of directly removing methyl groups from modified lysine residues has demonstrated that histone methylation is a dynamic modification. The most extensive family of histone demethylase enzymes identified so far contains a JmjC domain and catalyzes demethylation through a hydroxylation reaction. Here, we identify PLU-1, a transcriptional repressor implicated in breast cancer, as a histone demethylase enzyme that has the ability to reverse the trimethyl H3K4 modification state. Furthermore, we reveal that PLU-1-mediated H3K4 demethylase activity plays an important role in the proliferative capacity of breast cancer cells through repression of tumor suppressor genes, including BRCA1.